2022
DOI: 10.1186/s40068-022-00273-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability and trends of hydroclimatic variables at Zarima Sub-Basin North Western Ethiopia

Abstract: Globally, hydroclimatic variables have been changed due to human activities and have an impact on agricultural production and water resource management. This study investigated the spatio-temporal variability of hydroclimatic variables in Zarima subbasin using rainfall and temperature data from 1984 to 2018 and stream flow data from 1990 to 2014. The data were analyzed using the coefficient of variation, standardized anomaly index, Mann–Kendall trend and Sen’s slope estimator test. The results showed that rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In connection with this, the proximity of Ethiopia to the equator as well as the intricacy nature of the country's topography have a significant influence Ethiopia's climate, particularly the temperature [ 174 , 175 ]. Similarly, physical features such as terrain and sub-basin characteristics typically influence the spatial variability of maximum and minimum temperatures [ 120 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In connection with this, the proximity of Ethiopia to the equator as well as the intricacy nature of the country's topography have a significant influence Ethiopia's climate, particularly the temperature [ 174 , 175 ]. Similarly, physical features such as terrain and sub-basin characteristics typically influence the spatial variability of maximum and minimum temperatures [ 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the change in average annual maximum temperature across seasons, the highest temperature change occurred during the Belg season ( Table 1 ). In this regard, previous studies reported that the Belg season, which includes the months of March, April, and May, are the warmest months where the maximum temperature is recorded during this season [ 120 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like most African countries, developing countries are vulnerable to adverse impacts of climate change and variability because they have low adaptive capacity and high exposure as their economies rely mainly on agriculture. Among African regions, East Africa is the most vulnerable (Gebrechorkos et al, 2018;Zegeye et al, 2022;Gedefaw, 2023). In East Africa, agriculture contributes 30-50% of gross domestic product (GDP) and >80% of livelihood (FAO, 2014).…”
Section: Climate Change and Its Impactmentioning
confidence: 99%